Nutritional risk and its association with anthropometric, clinical and biochemical parameters in patients with chronic kidney disease on hemodialysis - Guimarães da Silva, Danielle Cristina; Souza, Lara Maria Novaes de; Mariano, Danielle Mendes; Cordeiro, Hemilly Lorrane Ribeiro; Ferreira, Fabrícia Geralda (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2025)
To investigate the association between higher nutritional risk and sociodemographic, anthropometric, clinical and biochemical parameters in hemodialysis patients. This is a cross-sectional study of adult and elderly patients with chronic kidney disease undergoing hemodialysis in Western Bahia. For the data collection, the modified subjective global assessment was used, anthropometric measurements were taken and clinical and biochemical data were obtained from the patients' medical records. Multiple linear regression analysis was used to assess the relationship between the highest score on the subjective global assessment and anthropometric, clinical and biochemical parameters. A total of 98 patients were assessed, 64.3% male and 59.2% aged between 35 and 59 years. The mean modified subjective global assessment score was 11,3±3,8. The prevalence of nutritional risk and malnutrition together was 73.3%. A positive association was found between higher nutritional risk and female sex (p=0.014), longer duration of hemodialysis treatment (p=0.010), higher serum potassium concentration (p=0.009) and higher pre-dialysis serum urea concentration (p=0.043). Higher nutritional risk is positively associated with female sex, longer hemodialysis treatment time, hyperpotassemia, and hyperphosphatemia in patients with chronic kidney disease.